Results of Reverse Transcription-Polymerase Chain Reaction (RT-PCR) Examination in Covid-19 Patients at Prof. Dr. H. Aloei Saboe City of Gorontalo - Nanang Roswita Paramata; Winansih Gubali; Rahma Yulia Adipu (Universitas Negeri Gorontalo, 2023)
Coronavirus Disease or COVID-19 is still a concern throughout the world. WHO recommends the Reverse Transcription-Polymerase Chain Reaction (RT-PCR) method as the gold standard for diagnosing COVID-19. The purpose of this study was to describe the results of the Reverse Transcription-Polymerase Chain Reaction (RT-PCR) examination in COVID-19 patients at Prof. Dr. H. Aloe Saboe, City of Gorontalo. This research is a type of descriptive qualitative research with a retrospective approach. The population of this study were all suspected and confirmed COVID-19 patients treated at Prof. Hospital. Dr. H. Aloe Saboe Gorontalo City in 2020-2021. The number of samples used was 344, using a purposive sampling technique. The research instrument used was medical record data. The results showed that the results of the Reverse Transcription-Polymerase Chain Reaction (RT-PCR) examination in COVID-19 patients at Prof. Dr. H. Aloei Saboe Gorontalo City in 2020-2021 the results obtained were 221 people positive (64.2%) and as many as 123 people (35.8%) negative